Analisa Fenomena Penggunaan Media Sosial Tiktok @duniaislam2 sebagai Media Dakwah - Ardana, Retno Anggraini Tri; Febriana, Poppy (Academicia Globe: Inderscience Research, 2020)
This study aims to analyze the motives of @duniaislam2 tiktok accounts in preaching on tiktok social media, using qualitative research methods and phenomenological approaches with Alfred Schutz theory, researchers use 3 informants who are usually account managers @duniaislam2serta in-depth observations and interviews are carried out in the data collection process. So that the results of the research were found to be Motives Because (becauses motives) informants do da'wah on Tiktok due to 2 things, namely the experience of informants who previously had difficulty getting Islamic da'wah information because they had to go to mosques or majlis to listen to lectures and also the experiences of informants because they were interested in ansihat – advice given by other preachers that can be a guide for their behavior in the future so that informants want to be like that. Furthermore, Motif For (in order to motives) in doing da'wah on social media dTiktok found the results that there is an ease of getting information about da'wah – Islamic da'wah, can provide advice to many people through @duniaislam2 account.